Measuring the Impact of Debt-Financed Public Investment - Cavalcanti, Carlos B. (The World Bank, 2014)
While debt-financed productive public investment raises a country's debt ratios in the short run, it can also generate higher growth, revenues, and exports, leading over time to lower debt ratios. This paper develops a framework to assess whether countries meet the conditions for realizing the net benefits over the costs of public investment debt financing. While it is possible to achieve debt sustainability with an appropriate mix of concessional and non-concessional financing, this is a necessary but not sufficient condition. It is also important to ensure the operational viability of public investment projects by having in place adequate project management: (i) project screening and appraisal, (ii) a clear connection between capital and recurrent expenditures once the projects are launched, and (iii) safeguards for appropriate project implementation and facilities operations. To illustrate the strength of these results, the paper carries out three measurement exercises: (a) a simulation of the degree to which the ratio of optimal public investment responds to changes in key parameters related to project management in a general equilibrium model; (b) application of the public investment management (PIMa) index to benchmark a country's public investment management capacity; and (c) presentation of the results of the Investment, Savings, and Macroeconomic Vulnerabilities tool aimed at tracking country choices in public finance and the impact of public projects on private investments